Strength enhancements across various parts in intermediate and edge stiffened angle sections due to cold-forming. (2022) - Deepak, M.S.; Beulah Gnana Ananthi, G.; Anupkumar, G. Ekbote; Harini, B.S.; Madhan Kumar, J.
Abstract: This study presents an experimental study on the strength characteristics of steel coupons extracted from various parts of Cold-Formed Steel (CFS) Intermediate and Edge Stiffened Angle Sections. The light gauge thin-walled CFS sections formed for specific design requisites are of different shapes, and often the profiles are stiffened by the employment of intermediate and edge stiffeners to resist elemental plate segment local buckling. As a result, these sections undergo modifications in their actual tensile strength characteristics across various regions, say the flat portions, corners and stiffened portions of the cross-section geometry due to the cold-forming from sheets into sections; hence is essential to know the stress-strain responses of the section before using them as structural members. Based on this study on various grades of stiffened angle sections, it is found that there is strength enhancement due to forming. Moreover, there is a notable increase in tensile capacities, say the maximum of 8% in the yield strength and a 5% increase in the ultimate strength in the corners and at the stiffened zones, with slightly less elongation capacity, in comparison with the tensile properties of flat parts. And also, there exists a marginal difference of 2–3% in the tensile properties between the partially stiffened and fully stiffened elemental parts of flat portions. These results can be effectively utilised while performing higher-order parametric studies by the Finite Element Analysis approach.